Application of Discovery Learning Model Based on Blended Learning to Activities and Learning Outcomes - Rifki Nomizar Khairani; A.K. Prodjosantoso (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to apply the Discovery Learning learning model based on Blended Learning to students' chemistry learning activities and outcomes. This research was conducted at SMA Negeri 5 Bengkulu City using the Classroom Action Research method. The implementation is carried out to find out problems in the learning process and steps that teachers can use to improve the quality of learning during the COVID-19 pandemic. The data collection technique in this study was a observation, interview, and test. The research shows that the activity and student learning outcomes increased, where the results of the proportion of student activity, teacher activity and the average student learning outcomes increased from cycle I to cycle II. Therefore, it can be concluded that the use of Discovery learning model based on blended learning can increase students' chemistry learning activities and results